Stainless steel built-up section stub columns: testing, numerical modelling and design - Jiang, Ke (2024)
This paper presents experimental and numerical investigations into the cross-sectional compressive behaviour and resistances of stainless steel built-up section stub columns. An experimental programme was firstly conducted on six built-up (open) I-sections and seven built-up (closed) tubular sections, with each composed of two identical press-braked stainless steel channel sections assembled by self-tapping screws, and included tensile coupon tests, initial local geometric imperfection measurements and twenty stub column tests. The experimental programme was followed by a numerical modelling programme, where finite element models were developed and validated against test results and then used to conduct parametric studies, aiming at investigating the effect of screw spacings and generating further numerical data over a wide range of cross-section dimensions. For the design of a stainless steel built-up section stub column, the current European code and American specification treat it as two individual channel section members and adopt effective width methods for calculating the cross-section compression resistance of each channel section member. Both design codes were found to result in many unsafe failure load predictions for stainless steel built-up I-section stub columns but conservative failure load predictions for stainless steel built-up tubular section stub columns. Finally, revised codified design rules were proposed by treating each built-up section as a whole and using an equivalent thickness of the overlapped plate elements, and shown to provide accurate, consistent and safe cross-section compression predictions for stainless steel built-up section stub columns.